A method for preparing molybdenum-rhenium alloy from molybdenum concentrate leaching solution and application thereof

CN122629332BActive Publication Date: 2026-10-13LUOYANG IND TECHNOLOGY RESEARCH INSTITUTE OF ZHENGZHOU UNIVERSITY +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611123251.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-13
Estimated Expiration
2046-07-28

AI Technical Summary

Technical Problem

这种将钼、铼分别提取、分别纯化、再机械混合的技术路线,流程冗长、能耗高、收率低,且无法从源头解决混合均匀性问题

Benefits of technology

[0067]本发明提供的钼铼共提取-共还原工艺,在原理上与传统固固掺杂具有本质差异。1、主元素共提取,而非微量掺杂:钼与铼均为主合金元素(铼含量可精确控制在3%~15%),通过共提取使钼、铼同步富集,没有任何一种元素被视作“掺杂剂”;2、钼铼混合溶液的共结晶保留分子级混合状态:采用喷雾干燥或快速蒸发,避免分步结晶,所得前驱体粉末中每一个微晶均同时含有钼酸铵与铼酸铵,其混合尺度达到纳米级乃至分子级。后续氢气还原时,钼与铼原子在还原瞬间即相互固溶,无需任何扩散过程;3、杂质含量更低:固固混合无法除去原材料固有的杂质元素,但共萃取过程本身具有选择性除杂能力(As、P、Fe等杂质留在萃余液),最终合金的W、Fe、K、Ca、Mg、Na、S、P等杂质总量比传统液液掺杂产品降低50%以上。典型分析显示,本工艺制备的钼铼合金纯度可达99.95%~99.98%,而传统液液掺杂法制备的类似材料纯度通常为99.8%~99.9%;4、性能大幅提升:分子级均匀混合使得铼效应得到最充分发挥。相同铼含量下,本工艺制备的合金其高温强度、延伸率提高50%~100%,再结晶温度提升200~500℃。核动力部件所要求的批次一致性显著优于传统工艺。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122629332B_ABST
    Figure CN122629332B_ABST
Patent Text Reader

Abstract

The application provides a method for preparing molybdenum-rhenium alloy from molybdenum concentrate leaching solution and application thereof. After molybdenum is extracted from molybdenum concentrate in a sulfur-phosphorus mixed acid system through circulation acid leaching and extraction, resin adsorption or extraction treatment is carried out to obtain an enrichment solution; then through desorption resin or back extraction, a mixed solution containing ammonium molybdate and ammonium rhenium acid is obtained, and then through drying, calcination and reduction, molybdenum-rhenium composite powder is obtained; after the molybdenum-rhenium composite powder is pressed, sintered and forged, molybdenum-rhenium alloy is obtained. The application starts from a new idea of "co-extraction-molecular level co-reduction", breaks through the limitations of long process, uneven element distribution and limited purity of traditional process for preparing molybdenum-rhenium alloy, innovatively proposes synchronous leaching and co-extraction of molybdenum and rhenium, realizes integrated preparation of atomic level uniform mixing of molybdenum and rhenium and reduction of impurity content, obtains resource full recovery and essential improvement of alloy performance, and provides molybdenum-rhenium alloy materials with excellent performance and independent controllability for nuclear power and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of comprehensive utilization technology of molybdenum concentrate, and relates to a method for preparing molybdenum-rhenium alloy from molybdenum concentrate leachate and its application, particularly a method for preparing alloy by simultaneous enrichment of molybdenum and rhenium from molybdenum concentrate leachate and its application. Background Technology

[0002] Molybdenum-rhenium alloys have significant applications in aerospace, nuclear energy, electronics, and high-temperature thermal components due to their excellent high-temperature strength, good plasticity, and radiation resistance. The addition of rhenium significantly improves the low-temperature brittleness and high-temperature creep resistance of molybdenum, a phenomenon known as the "rhenium effect." However, the alloy's properties are highly dependent on the uniformity of rhenium distribution within the molybdenum matrix.

[0003] Currently, the common method for preparing molybdenum-rhenium alloy precursor powders is to mechanically mix separately prepared molybdenum powder and rhenium powder. This solid-solid mixing method is limited by the differences in particle size and density between the two powders, making it difficult to achieve uniform mixing at the atomic / molecular level. Segregation and agglomeration during the mechanical mixing process can lead to problems such as compositional segregation, uneven microstructure, and unstable properties in the sintered alloy, thus limiting the development of high-end molybdenum-rhenium alloy materials.

[0004] Regarding raw material sources, rhenium is a rare and dispersed metal, mainly found as a byproduct of molybdenum and copper concentrates. Current processes typically recover rhenium from flue gas scrubbing liquid through roasting, leaching, and extraction / adsorption steps, while molybdenum is obtained through a separate crystallization and purification process. This technical route, which involves extracting, purifying, and then mechanically mixing molybdenum and rhenium separately, is lengthy, energy-intensive, and has a low yield, and it fails to address the issue of mixing uniformity at the source.

[0005] Therefore, developing a more suitable preparation method to solve the aforementioned technical problems in the preparation of molybdenum-rhenium alloys has become one of the urgent problems to be solved by many front-line researchers in the industry. Summary of the Invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a method for preparing molybdenum-rhenium alloy from molybdenum concentrate leaching solution and its application, particularly a method for simultaneously enriching molybdenum and rhenium in molybdenum concentrate leaching solution to prepare the alloy. The present invention can achieve simultaneous enrichment of molybdenum and rhenium in the liquid phase and ultimately directly prepare a molecularly homogeneous alloy precursor powder, while avoiding the inherent inhomogeneity of traditional mechanical mixing, thereby significantly improving the overall performance of the molybdenum-rhenium alloy. It also simplifies the process flow and improves the utilization rate of the rare and precious metal rhenium, which has significant technical and economic implications. The method provided by the present invention is simple, operates under mild conditions, has good stability, and is highly operable, making it more suitable for promotion and application in industrial production.

[0007] This invention provides a method for preparing molybdenum-rhenium alloy from molybdenum concentrate leaching solution, comprising the following steps:

[0008] 1) After leaching and extracting molybdenum from molybdenum concentrate in a sulfur-phosphorus mixed acid system, the post-molybdenum extraction liquid is obtained;

[0009] 2) After the molybdenum-extracted liquid obtained in the above steps is subjected to resin adsorption or extraction treatment, the adsorbed resin or enriched solution containing molybdenum and rhenium is obtained.

[0010] 3) Desorb the resin obtained from the above steps using ammonia water, or back-extract the enriched solution containing molybdenum and rhenium obtained from the above steps using ammonia water to obtain a mixed solution containing ammonium molybdate and ammonium rhenium.

[0011] 4) The mixed solution containing ammonium molybdate and ammonium rhenium obtained in the above steps is dried, calcined and reduced to obtain molybdenum-rhenium composite powder;

[0012] 5) The molybdenum-rhenium composite powder obtained in the above steps is pressed and sintered to obtain a molybdenum-rhenium alloy.

[0013] Preferably, the molybdenum concentrate, based on elemental mass content, comprises Mo: 50%~60%, S: 30%~40%, and Re: 15~40 g / t;

[0014] In the sulfuric acid-phosphoric acid mixed system, the concentration of sulfuric acid is 0.5~2.5 mol / L, and the concentration of phosphoric acid is 0.5~2.5 mol / L;

[0015] The cyclic acid leaching time is 1~4 h;

[0016] The temperature of the cyclic acid leaching is 70~120℃;

[0017] The liquid-to-solid ratio of the cyclic acid leaching is 5~15L / kg;

[0018] The number of cyclic acid leaching cycles is 5 to 15.

[0019] The extractant for molybdenum extraction includes P2O4.

[0020] Preferably, step 1) specifically comprises:

[0021] The molybdenum concentrate is leached in a sulfur-phosphorus mixed acid system to obtain a leachate. The leachate is then extracted to remove molybdenum, resulting in an acidic raffinate. This raffinate is then leached again with the next batch of molybdenum concentrate. After cyclic leaching and extraction of the raffinate to remove molybdenum, a rhenium-enriched raffinate is obtained.

[0022] The concentration of iron in the molybdenum extraction solution is 100-130 mg / L;

[0023] The concentration of vanadium in the molybdenum extraction solution is 150-180 mg / L.

[0024] The concentration of copper in the molybdenum extraction solution is 6000~7500 mg / L;

[0025] The concentration of rhenium in the molybdenum extraction solution is 40-60 mg / L;

[0026] The concentration of residual molybdenum in the molybdenum extraction solution is 1000~3000 mg / L.

[0027] Preferably, the resin used in the resin adsorption includes anion exchange resin or chelating resin;

[0028] The temperature at which the resin adsorbs is 20~60℃;

[0029] The resin adsorption time is 20~1200 min;

[0030] The extraction method includes multi-stage countercurrent extraction;

[0031] The extractant used in the extraction process includes amine extractants;

[0032] In the extraction process, the volume ratio of the organic phase to the aqueous phase is (0.5~3):1;

[0033] The extraction process is performed at a temperature of 20~60℃;

[0034] The extraction process takes 5 to 30 minutes.

[0035] Preferably, the mass concentration of the ammonia water is 5% to 15%;

[0036] The desorption treatment temperature is 20~80℃;

[0037] The desorption process takes 20-120 minutes.

[0038] The back-extraction temperature is 20~80℃;

[0039] The back-extraction time is 20-120 min;

[0040] In the mixed solution containing ammonium molybdate and ammonium rhenium, the mass ratio of molybdenum to rhenium is (15~25):1.

[0041] Preferably, the drying temperature is 90~120℃;

[0042] The drying time is 4~20 hours;

[0043] The calcination temperature is 470~550℃;

[0044] The calcination time is 3-5 hours.

[0045] Preferably, the reduction process includes a low-temperature reduction step and a high-temperature reduction step;

[0046] The reduction specifically involves using hydrogen gas for reduction;

[0047] The temperature for the low-temperature reduction is 480~530℃;

[0048] The low-temperature reduction time is 30~120 min;

[0049] The temperature for the high-temperature reduction is 820~920℃;

[0050] The high-temperature reduction time is 30~120 min;

[0051] The flow rate of the hydrogen gas is 15~20 m³. 3 / h.

[0052] Preferably, the oxygen content of the molybdenum-rhenium composite powder is less than or equal to 800 ppm;

[0053] The D50 particle size of the molybdenum-rhenium composite powder is 0.5~2 μm;

[0054] The pressing method includes cold isostatic pressing;

[0055] The pressure of the pressed blank is 200~250MPa;

[0056] The holding time for the pressed blank is 30-40 minutes;

[0057] The sintering specifically refers to sintering under a hydrogen atmosphere;

[0058] The sintering temperature is 1780~1850℃;

[0059] The holding time for sintering is 9-12 hours;

[0060] The hydrogen flow rate during the sintering process is 15~18 m³. 3 / h.

[0061] Preferably, after sintering, a forging step is also included;

[0062] The forging temperature is 1200~1500℃;

[0063] The total deformation during forging is 20% to 70%;

[0064] The molybdenum-rhenium alloy includes nuclear-grade molybdenum-rhenium alloy.

[0065] This invention provides the application of molybdenum-rhenium alloy prepared by the method described in any one of the above technical solutions in nuclear materials.

[0066] This invention provides a method for preparing molybdenum-rhenium alloy from molybdenum concentrate leaching solution, comprising the following steps: First, molybdenum concentrate is subjected to cyclic acid leaching and extraction in a sulfur-phosphorus mixed acid system to extract molybdenum, resulting in a post-molybdenum-extracted solution; then, the post-molybdenum-extracted solution obtained in the above step is subjected to resin adsorption or extraction treatment to obtain adsorbed resin or an organic phase containing molybdenum and rhenium; next, the adsorbed resin obtained in the above step is desorbed using ammonia water, or the organic phase containing molybdenum and rhenium obtained in the above step is back-extracted using ammonia water to obtain a mixed solution containing ammonium molybdate and ammonium rhenate; subsequently, the mixed solution containing ammonium molybdate and ammonium rhenate obtained in the above step is dried, calcined, and reduced to obtain molybdenum-rhenium composite powder; finally, the molybdenum-rhenium composite powder obtained in the above step is pressed and sintered to obtain a molybdenum-rhenium alloy. Compared with existing technologies, this invention creatively designs a specific process route for preparing molybdenum-rhenium alloys from molybdenum concentrate leachate. This is a method for simultaneously enriching molybdenum and rhenium in molybdenum concentrate leachate to prepare alloys. Starting from a novel approach of "co-extraction (co-reduction) of molybdenum and rhenium from molybdenum concentrate - molecular-level co-reduction," this invention overcomes the drawbacks of traditional processes that involve separate extraction and mechanical mixing of molybdenum and rhenium from molybdenum concentrate, resulting in lengthy processes, high energy consumption, and low yields. It also addresses the limitations of uneven element mixing caused by traditional solid-solid doping. This invention innovatively proposes simultaneous leaching and co-extraction of molybdenum and rhenium, achieving atomic-level uniform mixing of molybdenum and rhenium and integrated preparation with reduced impurity content. This results in complete resource recovery and a substantial improvement in alloy performance, providing high-performance, independently controllable molybdenum-rhenium alloy materials for fields such as nuclear power.

[0067] The molybdenum-rhenium co-extraction-co-reduction process provided by this invention differs fundamentally from traditional solid-solid doping in principle. 1. Co-extraction of main elements, rather than trace doping: Both molybdenum and rhenium are main alloying elements (rhenium content can be precisely controlled between 3% and 15%). Co-extraction allows for the simultaneous enrichment of molybdenum and rhenium, with neither element being considered a "dopant." 2. Co-crystallization of the molybdenum-rhenium mixed solution retains a molecular-level mixed state: Spray drying or rapid evaporation is used to avoid stepwise crystallization. Each microcrystal in the resulting precursor powder simultaneously contains ammonium molybdate and ammonium rheniumate, with the mixing scale reaching the nanometer or even molecular level. During subsequent hydrogen reduction, molybdenum and rhenium atoms instantly dissolve into each other without any diffusion process; 3. Lower impurity content: Solid-solid mixing cannot remove inherent impurity elements from the raw materials, but the co-extraction process itself has selective impurity removal capabilities (As, P, Fe, etc., remain in the raffinate), resulting in a final alloy with a total amount of impurities such as W, Fe, K, Ca, Mg, Na, S, and P that is more than 50% lower than that of traditional liquid-liquid doping products. Typical analysis shows that the purity of molybdenum-rhenium alloys prepared by this process can reach 99.95%~99.98%, while the purity of similar materials prepared by traditional liquid-liquid doping methods is usually 99.8%~99.9%; 4. Significantly improved performance: Molecular-level uniform mixing allows the rhenium effect to be fully utilized. At the same rhenium content, the alloys prepared by this process have 50%~100% higher high-temperature strength and elongation, and a 200~500℃ higher recrystallization temperature. The batch consistency required for nuclear power components is significantly better than that of traditional processes. Attached Figure Description

[0068] Figure 1 Electron micrograph and elemental distribution diagram of the molybdenum-rhenium composite powder prepared in Example 1 of this invention;

[0069] Figure 2 The image shows the electron backscatter diffraction (EBSD) pattern of the molybdenum-rhenium alloy prepared in Example 1 of this invention.

[0070] Figure 3 Electron micrograph and elemental distribution diagram of the molybdenum-rhenium composite powder prepared in Comparative Example 1 of this invention;

[0071] Figure 4 The image shows the electron backscatter diffraction (EBSD) pattern of the molybdenum-rhenium alloy prepared in Comparative Example 1 of this invention. Detailed Implementation

[0072] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims of the present invention.

[0073] There are no particular restrictions on the source of any raw materials used in this invention; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.

[0074] The purity of the raw materials used in this invention is not particularly limited. Preferably, the purity is analytical grade or conventional in the field of molybdenum concentrate separation and extraction.

[0075] All raw materials of this invention are conventional in the field, and each brand name and abbreviation is clear and distinct in its relevant application. Those skilled in the art can purchase them from the market or prepare them by conventional methods based on the brand name, abbreviation and corresponding application.

[0076] In all processes of this invention, the abbreviations are conventional abbreviations in the field. Each abbreviation is clear and unambiguous in its relevant application area, and those skilled in the art can understand its conventional process steps based on the abbreviation.

[0077] This invention provides a method for preparing molybdenum-rhenium alloy from molybdenum concentrate leaching solution, comprising the following steps:

[0078] 1) After leaching and extracting molybdenum from molybdenum concentrate in a sulfur-phosphorus mixed acid system, the post-molybdenum extraction liquid is obtained;

[0079] 2) After the molybdenum-extracted liquid obtained in the above steps is subjected to resin adsorption or extraction treatment, the adsorbed resin or enriched solution containing molybdenum and rhenium is obtained.

[0080] 3) Desorb the resin obtained from the above steps using ammonia water, or back-extract the enriched solution containing molybdenum and rhenium obtained from the above steps using ammonia water to obtain a mixed solution containing ammonium molybdate and ammonium rhenium.

[0081] 4) The mixed solution containing ammonium molybdate and ammonium rhenium obtained in the above steps is dried, calcined and reduced to obtain molybdenum-rhenium composite powder;

[0082] 5) The molybdenum-rhenium composite powder obtained in the above steps is pressed and sintered to obtain a molybdenum-rhenium alloy.

[0083] The present invention first involves leaching and extracting molybdenum from molybdenum concentrate in a sulfur-phosphorus mixed acid system to obtain a post-molybdenum extraction liquid.

[0084] In this invention, the molybdenum concentrate, based on elemental mass content, may include Mo: 50%~60%, S: 30%~40%, Re: 15~40 g / t, or Mo: 52%~58%, S: 32%~38%, Re: 20~35 g / t, or Mo: 54%~56%, S: 34%~36%, Re: 25~30 g / t.

[0085] In this invention, the concentration of sulfuric acid in the sulfuric-phosphoric acid mixed acid system can be 0.5~2.5 mol / L, 0.8~2.3 mol / L, or 1.0~2.0 mol / L. The concentration of phosphoric acid can be 0.5~2.5 mol / L, 0.8~2.3 mol / L, or 1.0~2.0 mol / L.

[0086] In this invention, the cyclic acid leaching time can be 1~4 h, 1.5~3.5 h, or 2.0~3.0 h.

[0087] In this invention, the temperature of the cyclic acid leaching can be 70~120℃, 80~110℃, or 90~100℃.

[0088] In this invention, the liquid-to-solid ratio of the cyclic acid leaching can be 5~15L / kg, 7~13L / kg, or 9~11L / kg.

[0089] In this invention, the number of cyclic acid leaching cycles can be 5 to 15 times, or 7 to 13 times, or 9 to 11 times.

[0090] In this invention, the extractant for extracting molybdenum preferably includes P204.

[0091] In this invention, step 1) can specifically be the following steps: leach molybdenum concentrate in a sulfur-phosphorus mixed acid system to obtain leachate, then extract molybdenum from the leachate to obtain molybdenum-extracted acidic raffinate, then leach it again with the next batch of molybdenum concentrate, and after cyclic leaching and extraction of raffinate to obtain rhenium-enriched molybdenum-extracted liquid.

[0092] In this invention, the concentration of iron in the molybdenum extraction solution can be 100~130 mg / L, or 105~125 mg / L, or 110~120 mg / L.

[0093] In this invention, the concentration of vanadium in the molybdenum extraction solution can be 150~180 mg / L, or 155~175 mg / L, or 160~170 mg / L.

[0094] In this invention, the concentration of copper in the molybdenum extraction solution can be 6000~7500 mg / L, or 6300~7200 mg / L, or 6500~7000 mg / L.

[0095] In this invention, the concentration of rhenium in the molybdenum extraction solution can be 40~60 mg / L, or 43~58 mg / L, or 45~55 mg / L.

[0096] In this invention, the concentration of residual molybdenum in the molybdenum extraction solution can be 1000~3000 mg / L.

[0097] The present invention further treats the molybdenum-extracted liquid obtained in the above steps with resin adsorption or extraction to obtain adsorbed resin or enriched solution containing molybdenum and rhenium.

[0098] In this invention, the resin used in the resin adsorption preferably includes anion exchange resin or chelating resin.

[0099] In this invention, the temperature at which the resin adsorbs can be 20~60℃, 25~55℃, 30~50℃, or 35~45℃.

[0100] In this invention, the resin adsorption time can be 20~1200min, 60~600min, or 90~300min.

[0101] In this invention, the extraction method preferably includes multi-stage countercurrent extraction.

[0102] In this invention, the extractant used in the extraction process preferably includes an amine extractant.

[0103] In this invention, the volume ratio of the organic phase to the aqueous phase in the extraction process can be (0.5~3):1, (1.0~2.5):1, or (1.5~2.0):1.

[0104] In this invention, the extraction temperature can be 20~60℃, 25~55℃, 30~50℃, or 35~45℃.

[0105] In this invention, the extraction time can be 5-30 min, 8-20 min, or 10-15 min.

[0106] The present invention then uses ammonia water to desorb the resin obtained in the above steps, or uses ammonia water to back-extract the enriched solution containing molybdenum and rhenium obtained in the above steps to obtain a mixed solution containing ammonium molybdate and ammonium rhenium.

[0107] In this invention, the mass concentration of the ammonia water can be 5%~15%, 7%~13%, or 9%~11%.

[0108] In this invention, the temperature of the desorption treatment can be 20~80℃, 30~70℃, or 40~60℃.

[0109] In this invention, the desorption treatment time can be 20~120 min, 40~100 min, or 60~80 min.

[0110] In this invention, a washing and impurity removal step is included before the back-extraction. Specifically, dilute sulfuric acid can be used for washing to remove metallic impurities.

[0111] In this invention, the back-extraction temperature can be 20~80℃, 30~70℃, or 40~60℃.

[0112] In this invention, the back-extraction time can be 20-120 min, 40-100 min, or 60-80 min.

[0113] In this invention, the mass ratio of molybdenum to rhenium in the mixed solution containing ammonium molybdate and ammonium rhenium is (15~25):1, which can be (17~19):1, (19~21):1, or (22~25):1.

[0114] The present invention then dries, calcines, and reduces the mixed solution containing ammonium molybdate and ammonium rhenium obtained in the above steps to obtain molybdenum-rhenium composite powder.

[0115] In this invention, the drying temperature can be 90~120℃, 95~115℃, or 100~110℃.

[0116] In this invention, the drying time can be 4~20h, 7~17h, or 10~14h.

[0117] In this invention, the calcination temperature can be 470~550℃, 480~540℃, 490~530℃, or 500~520℃.

[0118] In this invention, the calcination time can be 3~5h, 3.4~4.6h, or 3.8~4.2h.

[0119] In this invention, the reduction process preferably includes a low-temperature reduction step and a high-temperature reduction step.

[0120] In this invention, the reduction is preferably carried out using hydrogen gas.

[0121] In this invention, the temperature of the low-temperature reduction can be 480~530℃, 490~500℃, or 500~520℃.

[0122] In this invention, the low-temperature reduction time can be 30~120min, 50~100min, or 70~80min.

[0123] In this invention, the temperature of the high-temperature reduction can be 820~920℃, 840~900℃, or 860~880℃.

[0124] In this invention, the high-temperature reduction time can be 30~120min, 50~100min, or 70~80min.

[0125] In this invention, the flow rate of the hydrogen gas can be 15~20 m³. 3 / h, which can be 16~19 m 3 / h, which can be 17~18m 3 / h.

[0126] In this invention, the oxygen content of the molybdenum-rhenium composite powder can be less than or equal to 800 ppm, less than or equal to 750 ppm, or less than or equal to 700 ppm.

[0127] In this invention, the D50 particle size of the molybdenum-rhenium composite powder can be 0.5~2 μm, 0.7~1.8 μm, or 1.0~1.5 μm.

[0128] Finally, the molybdenum-rhenium composite powder obtained in the above steps is pressed and sintered to obtain a molybdenum-rhenium alloy.

[0129] In this invention, the pressing method preferably includes cold isostatic pressing.

[0130] In this invention, the pressure of the pressed blank can be 200~250MPa, 210~240MPa, or 220~230MPa.

[0131] In this invention, the holding time of the pressed blank can be 30~40min, 32~38min, or 34~36min.

[0132] In this invention, the sintering is preferably carried out in a hydrogen atmosphere.

[0133] In this invention, the sintering temperature can be 1780~1850℃, 1790~1840℃, 1800~1830℃, or 1810~1820℃.

[0134] In this invention, the sintering holding time can be 9~12h, 9.5~11.5h, or 10~11h.

[0135] In this invention, the hydrogen flow rate during the sintering process can be 15~18 m³. 3 / h can be 15.5~17.5m 3 / h, which can be 16~17 m 3 / h.

[0136] In this invention, the sintering process preferably includes a forging step.

[0137] In this invention, the forging temperature can be 1200~1500℃, 1250~1450℃, 1300~1400℃, or 1400~1500℃.

[0138] In this invention, the total deformation of the forging can be 20%~70%, 30%~60%, 40%~50%, or 60%~70%.

[0139] In this invention, the molybdenum-rhenium alloy preferably includes a nuclear-grade molybdenum-rhenium alloy.

[0140] This invention provides the application of molybdenum-rhenium alloy prepared by the method described in any one of the above technical solutions in nuclear materials.

[0141] This invention aims to complete and refine the overall technical solution, better ensure the composition and properties of molybdenum-rhenium alloys, and further improve the efficiency of preparing molybdenum-rhenium alloys from molybdenum concentrate leaching solutions. The aforementioned method for preparing molybdenum-rhenium alloys from molybdenum concentrate leaching solutions and its applications may specifically include the following:

[0142] A process for simultaneous enrichment of molybdenum and rhenium from molybdenum concentrate leaching solution and a method for alloy preparation, comprising the following steps:

[0143] S0. Molybdenum concentrate is subjected to multiple cycles of acid leaching and extraction in a sulfur-phosphorus mixed acid system to extract molybdenum. The raffinate is recycled for leaching. After extraction and molybdenum extraction, the molybdenum-extracted liquid is obtained.

[0144] S1. The molybdenum-extracted solution is treated by extraction or resin adsorption to simultaneously enrich molybdenum and rhenium in the solution, thereby obtaining an organic phase or resin loaded with molybdenum and rhenium.

[0145] S2. Desorb (desorb) the organic phase or resin loaded with molybdenum and rhenium using ammonia water to obtain a mixed solution containing ammonium molybdate and ammonium rheniumate;

[0146] S3. The molybdenum-rhenium composite powder is prepared by drying, calcining, and reducing the mixed solution containing ammonium molybdate and ammonium rhenium.

[0147] S4. A molybdenum-rhenium alloy is prepared by pressing, sintering, and forging the aforementioned molybdenum-rhenium composite powder.

[0148] Specifically, the molybdenum concentrate leaching solution is the molybdenum-extracting solution from the molybdenum concentrate sulfur-phosphorus mixed acid leaching solution.

[0149] Specifically, the solution after molybdenum extraction contains not only molybdenum and rhenium, but also impurities such as copper and iron.

[0150] Specifically, in step S1, when using the extraction method, the extractant used is an amine extractant.

[0151] Specifically, in step S1, when using the resin adsorption method, the resin used is anion exchange resin or chelating resin.

[0152] Specifically, in step S2, the concentration of the ammonia water is 5-15 wt%, the desorption / extraction temperature is 20-80℃, and the time is 10-120 min.

[0153] Specifically, in step S3, the mixed solution containing ammonium molybdate and ammonium rhenium is dried at 90-120℃ for 4-20 h to obtain the precursor; the precursor is calcined at 470-550℃ for 3-5 h, the low-temperature reduction temperature is 480-530℃, the high-temperature reduction temperature is 820-920℃, and the hydrogen flow rate is 15-20 m³ / h. 3 / h; The prepared molybdenum-rhenium composite powder has an oxygen content of less than or equal to 800 ppm, a particle size distribution D50 of 0.5~2 μm, and a loose packing density of 0.8~1.5 g / cm³. 3 It meets the stringent requirements for high-performance molybdenum-rhenium alloy raw materials.

[0154] Specifically, in step S4, cold isostatic pressing is used for compaction, with a pressure of 200~250MPa and a holding time of 30~40min; sintering is performed in a hydrogen atmosphere, with a sintering temperature of 1780~1850℃, a holding time of 9~12h, and a hydrogen flow rate of 15~18 m³ / h. 3 / h; the forging temperature is 1200~1500℃, and the deformation is 20%~70%.

[0155] Specifically, the prepared molybdenum-rhenium alloy has a density greater than 99%, a grain size less than 30 μm, a recrystallization temperature increased by more than 200℃, a high-temperature tensile strength of more than 400 MPa at 1100℃, and an elongation of more than 15%.

[0156] Specifically, the molybdenum-rhenium alloy powder prepared by this invention is used to prepare nuclear power components.

[0157] The present invention provides a method for preparing alloys by simultaneous enrichment of molybdenum and rhenium from molybdenum concentrate leaching solution and its application. Starting from a novel approach of "co-extraction of molybdenum and rhenium from molybdenum concentrate - molecular-level co-reduction," this invention overcomes the drawbacks of traditional processes that involve separate extraction and mechanical mixing of molybdenum and rhenium from molybdenum concentrate, resulting in lengthy processes, high energy consumption, and low yields. It also addresses the limitations of uneven element mixing caused by traditional solid-solid doping. The invention innovatively proposes simultaneous leaching and co-extraction of molybdenum and rhenium, achieving atomic-level uniform mixing of molybdenum and rhenium and integrated preparation with reduced impurity content. This results in complete resource recovery and a substantial improvement in alloy performance, providing high-performance, independently controllable molybdenum-rhenium alloy materials for fields such as nuclear power.

[0158] The molybdenum-rhenium co-extraction-co-reduction process provided by this invention differs fundamentally from traditional solid-solid doping in principle. 1. Co-extraction of main elements, not trace doping: Both molybdenum and rhenium are main alloying elements (rhenium content can be precisely controlled between 3% and 15%). Co-extraction allows for the simultaneous enrichment of molybdenum and rhenium, with neither element considered a "dopant." 2. Co-crystallization of the molybdenum-rhenium mixed solution retains a molecular-level mixed state: Spray drying or rapid evaporation avoids stepwise crystallization. Each microcrystal in the resulting precursor powder contains both ammonium molybdate and ammonium rhenate, with a mixing scale reaching the nanoscale or even molecular level. During subsequent hydrogen reduction, molybdenum and rhenium atoms instantly dissolve into each other without any diffusion process. 3. Lower impurity content: By eliminating the various additives required for traditional liquid-liquid doping, and because the co-extraction process itself has selective impurity removal capabilities (As, P, Fe, etc., remain in the raffinate), the total amount of impurities such as W, K, Ca, Mg, Na, and S in the final alloy is reduced by more than 50% compared to traditional liquid-liquid doped products. Typical analyses show that the purity of molybdenum-rhenium alloys prepared by this process can reach 99.95%~99.98%, while the purity of similar materials prepared by traditional liquid-liquid doping methods is typically 99.8%~99.9%. 4. Significantly improved performance: Molecular-level uniform mixing allows the rhenium effect to be fully utilized. At the same rhenium content, alloys prepared by this process exhibit 50%~100% higher high-temperature elongation and 200~500℃ higher recrystallization temperature. The batch consistency required for nuclear power components is significantly superior to that of traditional processes.

[0159] To further illustrate the present invention, the following describes in detail, with reference to embodiments, a method for preparing molybdenum-rhenium alloy from molybdenum concentrate leaching solution and its application. However, it should be understood that these embodiments are implemented under the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operating procedures. They are only for further illustrating the features and advantages of the present invention, and are not intended to limit the scope of the claims of the present invention. The scope of protection of the present invention is not limited to the following embodiments.

[0160] Example 1: A certain amount of molybdenum concentrate was subjected to cyclic leaching with a sulfuric-phosphoric acid mixture to enhance rhenium enrichment. The leaching conditions were: sulfuric acid (H2SO4) concentration 1.0 mol / L, phosphoric acid (H3PO4) concentration 1.5 mol / L, leaching temperature 80-95℃, and leaching time 3 hours. After solid-liquid separation, the leachate was used for molybdenum extraction. The acidic raffinate after molybdenum extraction was entirely recycled for the leaching of the next batch of molybdenum concentrate. After 10 cycles, the molybdenum-rhenium ratio was reduced, and the rhenium concentration in the leachate gradually increased. When the predetermined concentration was reached, a portion of the solution was withdrawn as downstream feedstock.

[0161] After cyclic enrichment, the main components of the extracted molybdenum solution were: Mo 1300 mg / L, Re 40 mg / L, Cu 6720 mg / L, Fe 108 mg / L, and V 150 mg / L. A kerosene solution containing 15% (v / v) N235 was used as the organic phase, and multi-stage countercurrent extraction was performed at room temperature (25℃) with a ratio O / A = 1:1 for 5 min. After extraction, the supported organic phase was back-extracted with a 10 wt% ammonia solution at 50℃ with a back-extraction ratio O / A = 2:1 for 30 min. The back-extraction yielded an ammonium molybdate / ammonium rhenium mixed solution enriched with molybdenum and rhenium.

[0162] The extraction rates were found to be 65% for molybdenum, >98% for rhenium, and less than 0.1% for impurity ions such as copper, iron, and vanadium, resulting in a mixed solution with a molybdenum-rhenium ratio of 21.5.

[0163] The mixed solution was dried in a forced-air drying oven at 110℃ for 12 hours. The dried powder was then placed in a muffle furnace and calcined at 500℃ for 4 hours to obtain molybdenum-rhenium composite oxide. The molybdenum-rhenium composite oxide was then subjected to a two-stage reduction in a hydrogen atmosphere. The hydrogen flow rate was 18 m³ / s. 3 / h. First, reduce at a low temperature of 500℃ for 90 minutes, then increase the temperature to 880℃ for a high temperature reduction of 90 minutes to obtain molybdenum-rhenium composite powder. The oxygen content of the powder was measured to be 600 ppm, and the D50 particle size was 1.2 μm.

[0164] The molybdenum-rhenium composite powder prepared in Example 1 of the present invention was characterized.

[0165] See Figure 1 , Figure 1 The images show electron micrographs and elemental distribution diagrams of the molybdenum-rhenium composite powder prepared in Example 1 of this invention. It can be seen that the molybdenum and rhenium are completely fused.

[0166] The molybdenum-rhenium composite powder was cold isostatically pressed at 230 MPa for 35 minutes. The preform was then subjected to a hydrogen atmosphere (hydrogen flow rate 16 m³ / s). 3The molybdenum-rhenium alloy ingot was sintered at a high temperature of 1820℃ for 10 hours. The sintered ingot was then forged at a roughing temperature of 1350℃ with a total deformation of 50%, ultimately yielding nuclear-grade molybdenum-rhenium alloy material. The alloy exhibited a density of 99.5%, a purity of 99.95%, an average grain size of 22.7 μm, a recrystallization temperature of 1400℃, a high-temperature tensile strength of 420 MPa at 1100℃, and an elongation of 21%.

[0167] The molybdenum-rhenium alloy prepared in Example 1 of the present invention was characterized.

[0168] See Figure 2 , Figure 2 The image shows the electron backscatter diffraction (EBSD) pattern of the molybdenum-rhenium alloy prepared in Example 1 of this invention.

[0169] Depend on Figure 2 It can be seen that due to the atomic-level uniform mixing, the "rhenium effect" (improving plasticity and reducing work hardening rate) is maximized. Even at the billet temperature of 1350℃, the material still has good hot workability. The dynamic recovery and recrystallization that occur under large deformation (50%) reach a dynamic equilibrium, which not only refines the grains (narrow strips) but also eliminates work hardening (fine equiaxed grains) through recrystallization.

[0170] Example 2: A molybdenum-extracted solution with the same composition as in Example 1 was taken, and the pH was adjusted to 2.0. It was then passed through an adsorption column packed with a strongly basic anion exchange resin (such as type D201) at a flow rate of 2 BV / h at 30°C for 60 min. After adsorption saturation, the resin bed was washed with deionized water. Subsequently, desorption was performed using an 8 wt% ammonia solution at 40°C at a flow rate of 1 BV / h for 30 min. The eluent was collected to obtain a mixed solution of ammonium molybdate and ammonium rheniumate.

[0171] The molybdenum recovery rate in the desorption solution was 60%, and the rhenium recovery rate was >99%, resulting in a mixed solution with a molybdenum-rhenium ratio of 19.69. The contents of impurities such as copper, iron, and vanadium in the desorption solution were extremely low.

[0172] The mixed solution was dried in a forced-air drying oven at 90℃ for 20 hours. The dried powder was then placed in a muffle furnace and calcined at 470℃ for 5 hours to obtain molybdenum-rhenium composite oxide. The molybdenum-rhenium composite oxide was then subjected to a two-stage reduction in a hydrogen atmosphere with a hydrogen flow rate of 15 m³ / h. 3 / h. First, reduce at a low temperature of 480℃ for 120 minutes, then increase the temperature to 820℃ for a high temperature reduction of 120 minutes to obtain molybdenum-rhenium composite powder. The oxygen content of the powder was measured to be 800 ppm, and the D50 particle size was 0.9 μm. The molybdenum-rhenium composite powder was then subjected to cold isostatic pressing at a pressure of 200 MPa for 40 minutes. The green body was then subjected to a hydrogen atmosphere (hydrogen flow rate 15 m³ / h).3 The molybdenum-rhenium alloy ingot was sintered at a high temperature of 1780℃ for 12 hours. The sintered ingot was then forged at a roughing temperature of 1450℃ with a total deformation of 70%, ultimately yielding nuclear-grade molybdenum-rhenium alloy material. The alloy exhibited a density of 99.2%, a purity of 99.97%, an average grain size of 19.5 μm, a recrystallization temperature of 1500℃, a high-temperature tensile strength of 450 MPa at 1100℃, and an elongation of 19%.

[0173] Example 3: A molybdenum-extracted solution with a composition similar to that of Example 1 was used. A kerosene solution containing 15% (v / v) N235 was used as the organic phase. Extraction was performed at 35°C with a ratio O / A = 2:1 for 8 min. The loaded organic phase was first washed with dilute sulfuric acid to remove some of the co-extracted iron, and then back-extracted with 12 wt% ammonia at 60°C for 30 min. This method achieved highly efficient and synergistic selective extraction of molybdenum (57% extraction rate) and rhenium (97% extraction rate), while also showing significant selective separation of iron. The iron concentration in the back-extraction solution was further reduced compared to Example 1, yielding a mixed solution with a molybdenum-rhenium ratio of 19.1.

[0174] The mixed solution was dried in a forced-air drying oven at 120°C for 4 hours. The dried powder was then placed in a muffle furnace and calcined at 550°C for 3 hours to obtain molybdenum-rhenium composite oxide. The molybdenum-rhenium composite oxide was then subjected to a two-stage reduction in a hydrogen atmosphere. The hydrogen flow rate was 20 m³ / s. 3 / h. First, reduce at a low temperature of 530℃ for 30 minutes, then increase the temperature to 920℃ for a high temperature reduction of 30 minutes to obtain molybdenum-rhenium composite powder. The oxygen content of the powder was measured to be 550 ppm, and the D50 particle size was 0.95 μm. The molybdenum-rhenium composite powder was then subjected to cold isostatic pressing at a pressure of 250 MPa for 30 minutes. The green body was then subjected to a hydrogen atmosphere (hydrogen flow rate 18 m³ / h). 3 The mixture undergoes high-temperature sintering at 1850℃ for 9 hours. The resulting molybdenum-rhenium alloy can be directly machined into the required components without forging. The molybdenum-rhenium alloy has a density of 99.1%, a purity of 99.98%, an average grain size of 28.3 μm, a recrystallization temperature of 1550℃, a high-temperature tensile strength of 410 MPa at 1100℃, and an elongation of 23%.

[0175] Comparative Example 1: Molybdenum powder and rhenium powder were mixed in a solid-solid manner, pressed into a blank, sintered, and forged to prepare a molybdenum-rhenium alloy.

[0176] According to the proportion of Example 1, 1075g of molybdenum powder and 50g of rhenium powder were weighed and mixed in a solid-solid manner for 48 hours. The solid-solid mixed powder was then processed using the same cold isostatic pressing (230 MPa, 35 min) and hydrogen sintering (1820℃, 10 h) process as in Example 1.

[0177] The molybdenum-rhenium composite powder prepared in Comparative Example 1 of this invention was characterized.

[0178] See Figure 3 , Figure 3 The image shows an electron microscope image and elemental distribution diagram of the molybdenum-rhenium composite powder prepared in Comparative Example 1 of this invention. It can be seen that molybdenum and rhenium exist as independent powders.

[0179] The sintered molybdenum-rhenium alloy ingot was forged using the same process as in Example 1, with a billet temperature of 1100℃ and a total deformation of 50%, ultimately yielding nuclear-grade molybdenum-rhenium alloy material. The molybdenum-rhenium alloy had a density of 93.2%, a purity of only 99.82%, an average grain size of 76.2 μm, a recrystallization temperature of 1150℃, a high-temperature tensile strength of 215 MPa at 1100℃, and an elongation of 11%.

[0180] The molybdenum-rhenium alloy prepared in Comparative Example 1 of this invention was characterized.

[0181] See Figure 4 , Figure 4 The image shows the electron backscatter diffraction (EBSD) pattern of the molybdenum-rhenium alloy prepared in Comparative Example 1 of this invention.

[0182] As shown in Figure 4, the uneven mixing limits the "rhenium effect," resulting in severe overall work hardening and significant localization of deformation. Under the same forging temperature (1350℃) and deformation amount (50%), the material exhibits greater rheological stress, and the deformation energy cannot be released through recrystallization. Instead, it can only coordinate deformation by forming large, wide strips. Furthermore, the absence of recrystallized grains indicates a large amount of residual internal stress within the material.

[0183] The final analysis of the metallographic structure of the alloy obtained in Comparative Example 1 revealed significant uneven distribution of rhenium and numerous pores. The alloy density was only 93.2%, far lower than the 99.5% density of the alloy prepared in Example 1. Furthermore, the overall process yield (from concentrate to alloy) of Comparative Example 1 was approximately 20 percentage points lower than that of Example 1, and the process was more complex, with a significant increase in acid and alkali consumption and wastewater volume.

[0184] The above provides a detailed description of a method for simultaneously enriching molybdenum and rhenium in molybdenum concentrate leachate to prepare alloys and its applications. Specific examples have been used to illustrate the principles and implementation methods of the invention. The descriptions of these embodiments are merely for the purpose of helping to understand the method and core ideas of the invention, including the best mode, and also to enable any person skilled in the art to practice the invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements that are not different from the wording of the claims, or if they include equivalent structural elements that are not substantially different from the wording of the claims, then these other embodiments should also be included within the scope of the claims.

Claims

1. A method for preparing molybdenum-rhenium alloy from molybdenum concentrate leaching solution, characterized in that, Includes the following steps: 1) After leaching and extracting molybdenum from molybdenum concentrate in a sulfur-phosphorus mixed acid system, the post-molybdenum extraction liquid is obtained; Step 1) specifically refers to: The molybdenum concentrate is leached in a sulfur-phosphorus mixed acid system to obtain a leachate. The leachate is then extracted to remove molybdenum, resulting in an acidic raffinate. This raffinate is then leached again with the next batch of molybdenum concentrate. After cyclic leaching and extraction of the raffinate to remove molybdenum, a rhenium-enriched raffinate is obtained. The concentration of rhenium in the molybdenum extraction solution is 40-60 mg / L; The concentration of residual molybdenum in the molybdenum extraction solution is 1000~3000 mg / L; 2) After the molybdenum-extracted liquid obtained in the above steps is subjected to resin adsorption or extraction treatment, the adsorbed resin or enriched solution containing molybdenum and rhenium is obtained. 3) Desorb the resin obtained from the above steps using ammonia water, or back-extract the enriched solution containing molybdenum and rhenium obtained from the above steps using ammonia water to obtain a mixed solution containing ammonium molybdate and ammonium rhenium. In the mixed solution containing ammonium molybdate and ammonium rhenium, the mass ratio of molybdenum to rhenium is (15~25):1; 4) The mixed solution containing ammonium molybdate and ammonium rhenium obtained in the above steps is dried, calcined and reduced to obtain molybdenum-rhenium composite powder; 5) The molybdenum-rhenium composite powder obtained in the above steps is pressed and sintered to obtain a molybdenum-rhenium alloy.

2. The method according to claim 1, characterized in that, The molybdenum concentrate, by elemental mass content, includes Mo: 50%~60%, S: 30%~40%, Re: 15~40 g / t; In the sulfuric acid-phosphoric acid mixed system, the concentration of sulfuric acid is 0.5~2.5 mol / L, and the concentration of phosphoric acid is 0.5~2.5 mol / L; The cyclic acid leaching time is 1~4 h; The temperature of the cyclic acid leaching is 70~120℃; The liquid-to-solid ratio of the cyclic acid leaching is 5~15L / kg; The number of cyclic acid leaching cycles is 5 to 15. The extractant for molybdenum extraction includes P2O4.

3. The method according to claim 1, characterized in that, The concentration of iron in the molybdenum extraction solution is 100~130 mg / L; The concentration of vanadium in the molybdenum extraction solution is 150-180 mg / L. The concentration of copper in the molybdenum extraction solution is 6000~7500 mg / L.

4. The method according to claim 1, characterized in that, The types of resins used in the resin adsorption include anion exchange resins or chelating resins. The temperature at which the resin adsorbs is 20~60℃; The resin adsorption time is 20~1200 min; The extraction method includes multi-stage countercurrent extraction; The extractant used in the extraction process includes amine extractants; In the extraction process, the volume ratio of the organic phase to the aqueous phase is (0.5~3):1; The extraction process is performed at a temperature of 20~60℃; The extraction process takes 5 to 30 minutes.

5. The method according to claim 1, characterized in that, The mass concentration of the ammonia solution is 5%~15%; The temperature for the desorption treatment is 20~80℃; The desorption process takes 20-120 minutes. The back-extraction temperature is 20~80℃; The back-extraction time is 20-120 min.

6. The method according to claim 1, characterized in that, The drying temperature is 90~120℃; The drying time is 4~20 hours; The calcination temperature is 470~550℃; The calcination time is 3-5 hours.

7. The method according to claim 1, characterized in that, The reduction process includes a low-temperature reduction step and a high-temperature reduction step; The reduction specifically involves using hydrogen gas for reduction; The temperature for the low-temperature reduction is 480~530℃; The low-temperature reduction time is 30~120 min; The temperature for the high-temperature reduction is 820~920℃; The high-temperature reduction time is 30~120 min; The flow rate of the hydrogen gas is 15~20 m³. 3 / h.

8. The method according to claim 1, characterized in that, The oxygen content of the molybdenum-rhenium composite powder is less than or equal to 800 ppm; The D50 particle size of the molybdenum-rhenium composite powder is 0.5~2 μm; The pressing method includes cold isostatic pressing; The pressure of the pressed blank is 200~250MPa; The holding time for the pressed blank is 30-40 minutes; The sintering specifically refers to sintering under a hydrogen atmosphere; The sintering temperature is 1780~1850℃; The holding time for sintering is 9-12 hours; The hydrogen flow rate during the sintering process is 15~18 m³. 3 / h.

9. The method according to claim 1, characterized in that, After sintering, a forging step is also included; The forging temperature is 1200~1500℃; The total deformation during forging is 20% to 70%; The molybdenum-rhenium alloy includes nuclear-grade molybdenum-rhenium alloy.

10. The application of the molybdenum-rhenium alloy prepared by the method according to any one of claims 1 to 9 in nuclear materials.

Citation Information

Patent Citations

  • Method for separating molybdenum and rhenium through extracting under acidic condition

    CN109055747A

  • Method for recovering tungsten and molybdenum from tungsten-containing low-grade molybdenum concentrate

    CN116411184A